Investigations into the Effects of pH, Sodium Chloride and Crude Oil on some Fungi Isolated from the Mangrove Forest in Port Harcourt, Nigeria - Ukoima, H. N.; Amakiri, M. A.; Adeniji, M. O.; Dan-Kalio, L. A. (Indian Forester, 2007)
Laboratory studies were conducted to determine the effects of pH and sodium chloride (NaCl) on the growth of Pestalotia dicheata (Speg) Stepaert and Fusarium moniliforme Sheldon isolated from Rhizophora mangle, Rhizophora harrisonii and Avicennia africana in Port- Harcourt, Nigeria. Similarly, the ability of fungi isolated from mangrove soil to grow on petroleum hydrocarbon was tested. The results obtained showed that the best pH range for the growth of P. dichaeta was pH4.0 (with mycelia dry weight of 0.927g).The least growth was in pH 3.0 (0.121g), while the best pH range for the growth of F. moniliforme was pH 8.0 (mycelia dry weight 1.363g) and the least pH which enhanced the growth of the fungus was pH 3.0 (mycelia dry weight 0.050g). The best sodium chloride chloride (NaCl) concentration that increased the growth of P. dichaeta was 20% NaCl (mycelia dry weight of 1.482g) and the least growth was obtained in 0% NaCl (mycelia dry weight 0.344g). These results were significant at (P< 0.05). The fungi isolated from mangrove soil which grew on petroleum hydrocarbon were : A. niger, A. flavus, Thielaviopsis basicola, Penicillium sp. and Fusarium sp.